DESAIN DAN ANALISIS VELG CAST WHEEL TIPE MT DAN WM DENGAN VARIASI SPOKE MENGGUNAKAN MATERIAL ALUMUNIUM ALLOY TIPE 7050-T7651 DAN 7075-T6 (SN) - Sobirin, Muhammad; P.N, Ardhi Fathonisyam; Bahri, Mokh. Hairul (Universitas Mercu Buana, 2025)
The automotive industry is growing rapidly. Produce changes, especially in the level of Safety and comfort. Vehicle manufacturers are competing to improve the quality of the components used in these vehicles. One aspect of Safety and comfort is the Safety and comfort of the vehicle's wheels, in addition to an attractive wheel design. Therefore, the material used on the wheels is high-quality, with precise calculations and correct designs. Vehicle wheels are one of the main components in vehicles because vehicles without wheels cannot run. There are two kinds of wheels: spoke wheels (spoke wheels) and cast wheels. This study aims to determine how to design cast wheel wheels type MT and WM and analyze material comparison and the number of spokes based on simulation using the software. The simulation results show the design of the MT-type cast wheel: the maximum stress value on the 7050-T7651 aluminum alloy material is 426.784 MPa, and on the 7075-T6 (SN) aluminum alloy material, which is 426.784 MPa, it is still within the safe limit because it is still below the value yield strength. In the design of the WM-type cast wheel, the maximum stress value on aluminum alloy type 7050-T7651 is 362085 MPa. On aluminum alloy material type 7075-T6 (SN), which is 362,085 MPa, it is still within safe limits because it is still below the yield strength value. The maximum strain value for the two materials used is 3.987 x 100-6, and the maximum displacement value for both materials is 9.959 x 100-4. The highest factor of safety value on WM 5 spoke wheels with aluminum alloy type 7050 –T7651 is 1.76